PEMBUATAN APLIKASI PENDATAAN DAN BOOKING ANTRIAN BEROBAT NARAPIDANA PADA KLINIK LAPAS BINJAI - Radiyan Rahim (CV. HAWARI, 2022)
Public servants have a function not only as meeting the basic needs of citizens as human beings but also providing protection to their citizens, kalapas clinic class 2 A Binjai is a special clinic that handles kalapas class 2 A Binjai inmates, The queuing system is a common activity carried out, including the kalapas clinic service every patient comes to take the queue then waits until he gets his turn and is served by the administration and get the treatment of a doctor Improving quality and service can be done by utilizing technology. This also adapts to the demands of a fast-paced era, all activities can be done only in the palm of your hand, this booking application will help patients in saving waiting time. In this application, patients can set a time for treatment with a doctor so that they do not have to wait for a long time at the clinic. Patients can come on a schedule that has been selected on the system. Officers will be helped when registering at the counter that has been provided, with this application there are no more files piled up due to crowded patient queues and other errors.